2001
DOI: 10.1111/1467-6494.696169
|View full text |Cite
|
Sign up to set email alerts
|

Individualism‐Collectivism and Personality

Abstract: This paper provides a review of the main findings concerning the relationship between the cultural syndromes of individualism and collectivism and personality. People in collectivist cultures, compared to people in individualist cultures, are likely to define themselves as aspects of groups, to give priority to in-group goals, to focus on context more than the content in making attributions and in communicating, to pay less attention to internal than to external processes as determinants of social behavior, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
1,288
5
73

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,806 publications
(1,468 citation statements)
references
References 47 publications
42
1,288
5
73
Order By: Relevance
“…That employee norms predicted both acceptability and norms is especially noteworthy and may reflect the Philippines' collectivist culture. In such a culture, peers have a strong influence on identity and behaviour (Triandis, 2001). This is perhaps even more important in government organisations whose leaders may keep changing and thus may not have permanent influence on culture.…”
Section: Discussionmentioning
confidence: 99%
“…That employee norms predicted both acceptability and norms is especially noteworthy and may reflect the Philippines' collectivist culture. In such a culture, peers have a strong influence on identity and behaviour (Triandis, 2001). This is perhaps even more important in government organisations whose leaders may keep changing and thus may not have permanent influence on culture.…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, los estudiantes franceses valoran más que los españoles el que los profesores promuevan la autonomía (Villasana & Alonso-Tapia, 2015), mientras que chilenos y españoles no difieren en su valoración de esa pauta; en cambio, los estudiantes chilenos valoran más que sus pares españoles que los profesores evalúen retroalimentando para mejorar a partir de los errores y que actúen equitativamente, entre otras. Estas diferencias no deberían sorprender, ya que diferentes culturas ponen de relieve valores u orientaciones que dan lugar a formas diferentes de valorar, comportarse y relacionarse (Triandis, 2001), de entender la competencia y la motivación (Plaut & Markus, 2005) y, como ya hemos mencionado, a culturas pedagógicas diferentes. No obstante, que sean esperables no exime de la tarea de conocerlas y hacerse cargo de ellas, pues para motivar a los estudiantes es necesario tener claridad respecto de cuáles son las pautas que tienen mayor relevancia para ellos a la hora de movilizarlos hacia el aprendizaje.…”
Section: Conclusionesunclassified
“…A second limitation is that it is conducted within an English-speaking, Western cultural setting. Research has shown that an individualÕs willingness to engage in deception and their reactions to deception vary by culture (Triandis, 2001;Triandis et al, 2001). Unfortunately, all of our flights originated or terminated in the United States and our observations excluded any non-English interactions.…”
mentioning
confidence: 92%